PERFORMANCE OF THE NURSE IN FRONT OF THE USER VICTIM OF TRAUMA CAUSED BY FIREARMS PROJECTILES: : AN EXPERIENCE REPORT - Eduarda Bezerra Lopes, Maria; Kácia Lopes Vieira, Werlídya; Souza Nascimento da Silva, Jacqueline; Clara Souza Lima, Ana; Barreto Pereira, Jéssica (Health and Society, 2021)
Firearm trauma is considered one of the main reasons for morbidity and mortality in Brazil. In view of its destructive capacity of organs and tissues that come into contact with the fragments of the bullet. This work aims to report the experience of three students of the nursing course, facing the care of a patient with a firearm. This is a descriptive, qualitative, experience report type study. In the present study, it was possible to envision the application of the nursing process in its entirety, which allowed us to think of a plan based on the process of rehabilitation and healing of the patient. Going up a discussion about the violence in the country, since it is taking a high mortality rate between 15 to 24 years. Based on the construction of this work, it is suggested to create new research that addresses in a qualitative and quantitative way the impact of cases of violence in today's society.